Differential expression of stem cell markers and ABCG2 in recurrent prostate cancer. Issue 15 (29th August 2014) - Guzel, Esra; Karatas, Omer F.; Duz, Mehmet B.; Solak, Mustafa; Ittmann, Michael; Ozen, Mustafa
<x xml:space="preserve">Abstract</x> BACKGROUND Prostate cancer (PCa) is the second most common tumor type related to mortality in males in the developed countries. Studies have demonstrated that therapeutic tools mostly ineffective to give positive outcome especially for PCa. Cancer stem cells are composed of a small cell population, which are supposed to have roles in tumorigenesis, metastasis, and tumor recurrence after chemo‐radiotherapy. The aim of this research is to investigate expressions of stem cell markers in recurrent PCa and non‐recurrent PCa tumors as well as in adjacent normal prostate tissues. METHODS We compared the expression of important stemness regulators like SOX2, OCT4, KLF4, and ABCG2 in recurrent, non‐recurrent PCa and adjacent normal tissue samples using quantitative real‐time polymerase chain reaction (qRT‐PCR). RESULTS Our results demonstrated that SOX2 and OCT4 are strongly overexpressed in PCa samples. Recurrent PCa samples are markedly positive for stem cell markers SOX2, OCT4, and KLF4. Furthermore, non‐recurrent PCa samples presented low levels of ABCG2, a multidrug resistance protein, compared to both normal and recurrent samples, which might be associated with chemo‐sensitivity. CONCLUSIONS Enhanced expression of ABCG2 and stem cell markers including SOX2, OCT4, and KLF4 in the recurrent PCa tissues postulates the suggestion that enrichment for cells with stem cell characteristics in these tissues might be playing a critical role for chemoresistance and recurrence of cancer. Prostate 74:1498–1505, 2014. © 2014 Wiley Periodicals, Inc.